Implementasi Metode Dempster Shafer Analytic Hierarchy Process Untuk Pemilihan Program Studi Calon Mahasiswa - Pangestika, Menur Wahyu; Nurhayati, Oky Dwi; Suryono, Suryono (JSINBIS (Jurnal Sistem Informasi Bisnis), 2016)
Methods Dempster Shafer Analytic Hierarchy Process is used to rank or sort information based on a number of criteria. DS/AHP advantage of Pairwise Comparison, Consistency Ratio, and Dempster Rule's of Combination, which is used to generate information systems in the form of a sequence of courses as consideration for the selection of majors for prospective students. The sample used in this study were 29 students of five faculty at the University of Diponegoro. The data used is the standard minimum value of each faculty and the average value of the semester report card 1-5 Mathematics, Indonesian, English, Biology, Chemistry, and Physics. Results of this study was the software selection study program that gives students the value of trust in each department. Testing the validity of the value of the accuracy of the system is done by comparing the majors were chosen with the recommendation majors produced by the system, resulting accuracy of 79.33%.